Removal of Cadmium using Alkaline-Treated Activated Carbon from Leucaena Leucocephala Biomass - W.M.H.W. Ibrahim; N.S. Sulaiman; M.H.M. Amini; W.R.A. Kadir; M. Mohamed; S.F.M. Ramle; U. Bilgin; W. Rahman (Archives of Metallurgy and Materials, 2022)
Water contamination that caused by heavy metals is a very common phenomenon in the industrial age. One of the popular way to treat metal contaminated water is by adsorption process using activated carbon as the adsorbent. This paper works on producing activated carbon by chemical means with impregnation ratios of NaOH:char (w/w) was predetermined at 1:1 (ACT1-1), 2:1 (ACT2-1) and 3:1 (ACT3-1) under activation temperature of 700°C. Considering the Leucaena leucocephala is a wildly, easy and fast grown species, with the availability throught the year, it was chosen to be used as the precursor. The properties of these activated carbons and its potential for cadmium removal from aqueus solution was analyzed. It was found that the highest surface area was recorded at 662.76 m²/g. Four parameters were studied which are contact time, the effect of pH, initial concentration of adsorbate and temperature. The equilibrium time was achieved in 40 min treatment at initial concentrations of 30 mg/l. The adsorbent exhibited good sorption potential for cadmium at pH 8.0 and equilibrium temperature of 30℃. Based on the results, this study had proved that activated carbon from Leucaena leucocephala biomass have the good potential to be used for removal of cadmium from wastewater.